Usos e interpretaciones profético-materialistas de El capital - Martínez Andrade, Luis (2022)
The link between Marxism and Liberation Theology has been explored by some researchers to account for the elective affinity between these currents of thought. This article analyses the reading of Capital that someliberation theologians have made, while showing how these theologians have incorporated it into their theoretical project.